Journey around Maine from A to Z - Zschock, Martha Day. (Beverly, Mass. : Commonwealth Editions, 2007)
Travel around Maine visiting historical landmarks, shipbuilding sites, and ocean coasts, while learning about the heritage and animals of the state.
Keywords: English language -- Alphabet -- Juvenile literature; Alliteration -- Juvenile literature; Maine -- Juvenile literature